Institutional distrust among gay, bisexual, and other men who have sex with men as a barrier to accessing pre-exposure prophylaxis (PrEP). Issue 3 (4th March 2019) - Peterson, Meghan; Nowotny, Kathryn; Dauria, Emily; Arnold, Trisha; Brinkley-Rubinstein, Lauren
ABSTRACT: Populations at highest risk for acquiring HIV are more likely to pass through criminal justice (CJ) settings, and CJ-involved individuals are often at the intersection of multiple overlapping risk factors. The present study explored interest in, knowledge of, and barriers to PrEP uptake among gay, bisexual, and other men who have sex with men involved in the criminal justice system. Using semi-structured interviews, 26 participants who identified as MSM were asked about PrEP knowledge and interest, HIV risk, and incarceration experience. One theme that emerged across interviews was how institutional distrust in CJ settings may instill lack of trust in medical care after perceived mistreatment. Participants explained how lack of privacy fostered feelings that medical care was not confidential, care received was tied to status as an incarcerated person, and feelings of dehumanization led to distrust. Findings explore how distrust may hinder PrEP uptake and other HIV prevention efforts in CJ settings as well as after release. They highlight the need for greater privacy efforts and cultural humility, and explore how medical settings may function as spaces for people who are incarcerated to disclose HIV risk status. Few studies to our knowledge have examined the role of institutional distrust on men who have sex with men (MSM) in the context of pre-exposure prophylaxis (PrEP) interventions. The present study has implications for creating best practices to structure HIV prevention interventions in CJ settings.